2017
DOI: 10.1101/128124
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defects of myelination are common pathophysiology in syndromic and idiopathic autism spectrum disorder

Abstract: Autism Spectrum Disorder (ASD) is genetically heterogeneous in nature with convergent symptomatology, suggesting dysregulation of common molecular pathways. We analyzed transcriptional changes in the brains of five independent mouse models of Pitt-Hopkins Syndrome (PTHS), a syndromic ASD caused by autosomal dominant mutation in TCF4, and identified considerable overlap in differentially expressed genes (DEGs). Gene and cell-type enrichment analyses of these DEGs identified oligodendrocyte dysregulation that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Alterations in corpus callosum morphology and in the development of white matter microstructure in early ASD implicates processes governing myelination, axon caliber, density and axonal connectivity. A study of several mouse models of ASD recently identified a significant enrichment of myelination genes, and gene-set analysis implicated genes and pathways associated with myelination and oligodendrocyte differentiation 139 . Altered oligodendrocyte function has been documented in Pten-mutant mouse models of ASD, such that oligodendrocyte progenitor cells developed too early, resulting in reduced myelin sheaths 140 , which would impede information transfer along axons.…”
Section: Candidate Neurobiological Mechanismsmentioning
confidence: 99%
“…Alterations in corpus callosum morphology and in the development of white matter microstructure in early ASD implicates processes governing myelination, axon caliber, density and axonal connectivity. A study of several mouse models of ASD recently identified a significant enrichment of myelination genes, and gene-set analysis implicated genes and pathways associated with myelination and oligodendrocyte differentiation 139 . Altered oligodendrocyte function has been documented in Pten-mutant mouse models of ASD, such that oligodendrocyte progenitor cells developed too early, resulting in reduced myelin sheaths 140 , which would impede information transfer along axons.…”
Section: Candidate Neurobiological Mechanismsmentioning
confidence: 99%